THEORETICAL MODEL OF PROFESSIONAL DEFORMATION AMONG MILITARY PSYCHOLOGIST OF THE NATIONAL GUARD OF UKRAINE UNDER MARTIAL LAW - Onyshchuk, Kristina (Honor and Law, 2025)
The paper examines the differentiation between the concepts of professional deformation and professional burnout and substantiates the causes of terminological discrepancies between Ukrainian and foreign scholarly traditions. An authorial model of the professional deformation of military psychologists is proposed.